Impact of a Submaximal Warm-Up on Endurance Performance in Highly Trained and Competitive Male Runners. Issue 1 (2nd January 2017) - Zourdos, Michael C.; Bazyler, Caleb D.; Jo, Edward; Khamoui, Andy V.; Park, Bong-Sup; Lee, Sang-Rok; Panton, Lynn B.; Kim, Jeong-Su
Abstract : Purpose: The purpose of this investigation was to examine the effects of a submaximal running warm-up on running performance in male endurance athletes ( n  = 16, M age  = 21 ± 2 years, M VO2max  = 69.3 ± 5.1 mL/kg/min).Method: Endurance performance was determined by a 30-min distance trial after control and submaximal running warm-up conditions in a randomized crossover fashion. The warm-up began with 5 min of quiet sitting, followed by 6 min of submaximal running split into 2-min intervals at speeds corresponding to 45%, 55%, and 65% maximal oxygen consumption (VO2 max). A 2-min walk at 3.2 km/hr concluded the 13-min warm-up protocol. For the control condition, participants sat quietly for 13 min. VO2 and heart rate (HR) were determined at Minutes 0, 5, and 13 of the pre-exercise protocol in each condition.Results: At the end of 13 min prior to the distance trial, mean VO2 (warm-up = 14.1 ± 2.2 mL/kg/min vs. control = 5.5 ± 1.7 mL/kg/min) and mean HR (warm-up = 105 ± 11 bpm vs. control = 67 ± 11 bpm) were statistically greater ( p  < .001) in the warm-up condition compared with the control condition. The distance run did not statistically differ ( p  = .37) between the warm-up (7.8 ± 0.5 km) and control (7.7 ± 0.6 km) conditions; however, effect size calculation revealed a small effect ( d  = 0.2) in favor of the warm-up condition. Thus, the warm-up employed may have important and practical implications to determine placing among high-level athletes in close races.Conclusions: These findings suggest a submaximal running warm-up may have a small but critical effect on a 30-min distance trial in competitive endurance athletes. Further, the warm-up elicited increases in physiological variables VO2 and HR prior to performance; thus, a submaximal specific warm-up should warrant consideration.